Pelatihan Dasar Adobe Photoshop dan Penggunaan AI pada CV Barata Batik - Febrian, Angga; Adrian, Qadhli Jafar; Husna, Nurul Husna; Mawardi , M. Wildhan Ar; Setiaji, Rangga; Hutagalung, Samuel (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: CV Barata Batik has not been able to maximize technology and the internet into its business processes. The service team formulated several solutions to overcome this with professional graphic design training conducted to improve performance to make it more effective and efficient. Research methodology: The method of implementing this activity aims to improve the understanding and skills of batik craftsmen. It involves the use of Adobe Photoshop and artificial intelligence (AI) such as ChatGPT and Adobe Firefly in batik design, allowing creative exploration, idea development, and mockup creation. A competency-based approach encourages the development of practical skills, while a convenient training location at the Horison Bandar Lampung Hotel supports the effectiveness of the training. Results: The discussions that were carried out resulted in the conclusion that the service participants felt very satisfied and happy with the training they received. In fact, there was a request from the participants to continue a similar program on an ongoing basis. Limitation: The discussion may be limited to the context of CV Barata Batik, so readers from other industries may find it less relevant. Cotribution: Through community service carried out by a team from the University of Lampung and the Indonesian Technocrat University, the cooperation in maximizing technology.